2000
DOI: 10.1007/s11738-000-0090-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phytohormones and tungsten on light-induced and nitrate-induced nitrate reductase activity of mustard cotyledons

Abstract: Mustard (Brassica flmcea Coss cv. T-59 'Varuna') seedlings pretreated with gibberellic acid (GA) and kinetin (KIN) were grown in light. In vivo nitrate reductase (NR) activity was estimated and effect of tungsten on light-induced and NO3-induced NR activity was investigated. Different concentrations of GA did not show any effect on induction of light-induced NR; addition of nitrate promoted in vivo NR activity but no concentration effect of GA was evident. Light-induced NR was promoted by KiN and like in GA tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…However, Leleu and Vuylsteker (2004) reported that NRA in Brassica napus seedlings was independent of nitrate content and that both NRA and NR mRNA accumulation was much larger with sole NH 4 + provision than those with NO 3 -provision only. Saroop et al (2000) also showed that the nitrate is not required when NR was induced by light treatment in mustard (Brassica Juncea). Moreover, ammonium induced NRA in maize leaves only under light-incubated conditions (Mehta and Srivastava 1980).…”
Section: Discussionmentioning
confidence: 97%
“…However, Leleu and Vuylsteker (2004) reported that NRA in Brassica napus seedlings was independent of nitrate content and that both NRA and NR mRNA accumulation was much larger with sole NH 4 + provision than those with NO 3 -provision only. Saroop et al (2000) also showed that the nitrate is not required when NR was induced by light treatment in mustard (Brassica Juncea). Moreover, ammonium induced NRA in maize leaves only under light-incubated conditions (Mehta and Srivastava 1980).…”
Section: Discussionmentioning
confidence: 97%
“…35,36 Indeed, some authors reported a light-induced NR independent of NO 3 − in some species. 37,38 Its regulation seems to be different to the NO 3 − -induced NR 39 and its function remains to be elucidated. In this context, it is possible that the enhanced NR activity in presence of urea observed in our experiment could be due to an induction of a NO 3 − -independent NR.…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, a significant decrease in nitrogenase activity of several free living N 2 fixing bacteria in the presence of W was reported. ,, Although the exact toxicity mechanism is not known, it was suggested that a replacement of Mo by W renders the N 2 -fixing nitrogenase enzyme inactive . Also, the activity of nitrate reductase, a molybdoenzyme responsible for the assimilatory reduction of nitrate to nitrite, was repeatedly shown to be inhibited in the presence of monomeric tungstate with its negative effect again being attributed to the prevention of the formation of an active Mo cofactor required for NR catalytic activity. Deng et al found that W inactivated NR but simultaneously increased NR protein abundance and corresponding mRNA tissue concentrations, leading to an over-expression of the NR genes. In our study, W had contrasting effects on the interrelated activities of the studied molybdoenzymes (i.e., nitrate reductase, and nitrogenase, respectively) in nodulated soybeans, indicating complex interactions between (pH-dependent) W solubility and speciation, pH and texture-driven organic N mineralization and stabilization, and molybdoenzyme-driven plant N nutrition.…”
Section: Discussionmentioning
confidence: 99%